Mechanical and morphological properties of twill glass fiber reinforced lignin/epoxy composites: An experimental study - Celiktas, Melih Soner; Uyan, Merve; Farshid, Khosravi Maleki (Nova Science Publishers, Inc., 2021)
The increase in environmental concerns due to fossil resource consumption resulted in the development of bio-renewable polymer-based materials, products, and processes. Lignin, which is among the biorenewable polymers, is the most abundant natural polymer after cellulose in the lignocellulosic structure. In this study, the effects of lignin supplementation to epoxy resin in the matrix phase on the mechanical and morphological properties of twill glass fiber composite material were investigated experimentally. The resin mixtures which were the matrix material of the composite were prepared according to 4 different ratios (0, 1, 3, 5% alkali lignin) and the mixtures were used in the production of four different composite materials. The mechanical properties (tensile strength, fracture toughness) and morphological properties (SEM and EDS analysis) of the produced lignin reinforced composite materials were analyzed and compared with each other. The results show that 3% alkali lignin reinforced composite reached the highest elasticity modulus (15GPa) and showed close tensile strength (255 MPa) with 0% alkali lignin reinforced composite (273 MPa). In this paper, it was observed that by adding lignin to the composite the modulus of elasticity was improved. Therefore, the sample weight was reduced. The properties achieved enables consideration of the produced lignin reinforced composites as competitive alternatives for commercial composites. Lignin has the potential to be used for the development of new polymer composite materials with its impressive properties, such as low weight, environmental friendliness, and biodegradability. In order to show the potential usage these produced materials, small scale wind turbine blade production was performed in labscale. The production of airfoils for small scale wind turbine (SSWT) blades was carried out at 3% and 0% alkali lignin ratio and it was found that they had close Cp values according to the wind tunnel tests applied to the SSWT blades. © 2021 Elsevier B.V., All rights reserved.
Keywords: Composite; Lignin; Mechanical Test; Sem Analysis; Wind Turbine Blade